Intraoperative electrochemotherapy of colorectal liver metastases: A prospective phase II study. Issue 9 (September 2020) - Edhemovic, Ibrahim; Brecelj, Erik; Cemazar, Maja; Boc, Nina; Trotovsek, Blaz; Djokic, Mihajlo; Dezman, Rok; Ivanecz, Arpad; Potrc, Stojan; Bosnjak, Masa; Markelc, Bostjan; Kos, Bor; et al.
Abstract: Background and objectives: A previous pilot study proved the feasibility, safety and efficacy of electrochemotherapy in the treatment of colorectal liver metastases. The aim of this study was to evaluate long-term effectiveness and safety of electrochemotherapy in the treatment of unresectable colorectal liver metastases. Patients and methods: In this prospective phase II study, patients with metachronous colorectal liver metastases were included. In all patients, at least one metastasis was unresectable due to its central location or a too-small future remnant liver volume. Patients were treated by electrochemotherapy using intravenously administered bleomycin during open surgery. Treated were 84 metastases in 39 patients. Local tumor control, progression-free survival and overall survival were evaluated. Results: The objective response was 75% (63% CR, 12% PR). The median duration of the response was 20.8 months for metastases in CR and 9.8 months for metastases in PR. The therapy was significantly more effective for metastases smaller than 3 cm in diameter than for larger ones. There was no difference in response according to the metastatic location, i.e., metastases in central vs. peripheral locations. Progression-free survival was better in patients who responded well to electrochemotherapy compared to those metastases that had a partial response or progressive disease. However, there was no difference in overall survival, with a median of 29.0 months. Conclusions: Electrochemotherapy has proven to be safe and effective in the treatment of colorectal liver metastases, with a durable response. It provides local tumor control that enables patients with unresectable metastases to receive further treatments. Highlights: The objective response of electrochemotherapy-treated colorectal liver metastases is 75%. Electrochemotherapy is equally effective on metastases located either in the vicinity of or away from major liver blood vessels. Metastases smaller than 3 cm respond better than larger ones. The overall survival of the patients with unresectable colorectal liver metastases resistant to standard chemotherapy after electrochemotherapy was 29 months.